(untitled) (Research, Society and Development, 2021)
Brazilian agriculture is largely dependent on soluble chemical fertilizers. However, there are alternatives such as rock dust, a waste from mining, which has residual power to release nutrients. The objective of this work was to evaluate the fourth-year residual effect of stonemeal on chemical, microbiological and nutritional status of soybean crop. The experiment was carried out at the Experimental Farm of UFGD, in Dourados (MS), in a Dystroferric Red Latosol. The experimental design was in randomized split plots per block, with four replications. The plots contained the doses (0, 2.5, 5.0, 7.5 and 10 Mg.ha-1) and the subplots chemical fertilization (with and without fertilization). After harvesting, soil samples of 0-10 and 10-20 cm were collected for chemical analysis. For microbiological analysis, soil samples were collected at 10 cm from soybean flowering to evaluate qCO2 and qMIC. For the nutritional status of the crop, the third trefoil with petiole at stage R2 was collected. Data were subjected to analysis of variance, means compared by Student’s t test at 5% and for doses (significant) there was regression analysis. The rock powder influenced the Fe contents, from 0-10 cm, and the pH H2O and Mn at 10-20 cm. In the leaf analysis, there was an interaction between doses of basalt and fertilization for P and isolated effect of doses for K, Ca and Mn. The residual effect of basaltic rockstone can affect soil chemical attributes and crop nutrition.